Recursive macroeconomic theory - Ljungqvist, Lars.; Sargent, Thomas J. (Cambridge, Mass. : MIT Press, 2000)
The book offers a powerful approach in dynamic macroeconomics, It contains both an introduction to recursive tools including standard applications such asset pricing and advanced material including analyses of reputational mechanisms and contract design
Includes bibliographical references (p. [665]-692) and indexes.
opc01/11/13
Loans
Keywords: Recursive functions; Macroeconomics; Statics and dynamics (Social sciences)